Pd-Catalyzed N–H or C–H Functionalization/Oxidative Cyclization for the Efficient Synthesis of N-Aryl-Substituted [3,4]-Fused Pyrrolocoumarins - Balalas, Thomas D.; Kanelli, Maria G.; Gabriel, Catherine; Pontiki, Eleni; Hadjipavlou-Litina, Dimitra J.; Litinas, Konstantinos E. (Synthesis, 2022)
1-Aryl-2-methyl- or 3-methylchromeno[4,3-b]pyrrol-4(1H)-ones have been synthesized in excellent yields by the Pd-catalyzed intramolecular aza-Wacker-type cyclization of 3-allyl-4-arylaminocoumarins or C–H insertion/oxidative cyclization of N-allyl-N-aryl-4-aminocoumarins, respectively, in the presence of Cu(OAc)2 in acetic acid under heating. The starting allylcoumarins have been prepared by the allylation of 4-arylaminocoumarins with allyl bromide in CH3CN in the presence of Cs2CO3 at room temperature. Preliminary biological tests indicated interesting antioxidant activity and significant levels of inhibition of soybean lipoxygenase.
Keywords: [3,4]-fused pyrrolocoumarins; Pd-catalyzed aza-Wacker oxidative cyclization; copper acetate; 3-allyl-4-arylaminocoumarins; N-allyl-N-aryl-4-aminocoumarins